PENERAPAN MODEL PROBLEM BASED LEARNING MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS - Auliah Sumitro H; Punaji Setyosari; Sumarmi Sumarmi (Graduate School of Universitas Negeri Malang, 2017)
This research aims to improve motivation and student learning outcomes in applying Problem Based Learning model. This research is a classroom action research conducted in two cycles. The subjects of the reasearch was the fourth graders of SD Inpres Bangkala III Makassar city in the academic year of 2016/2017. The research data obtained through observation and test. The result showed an increase in student motivation of the fourth aspect with detail, on aspect of attention increased by 11,28% from 73,04 in the first cycle to 84,32% in the second cycle, the relevance aspect increasde by 9,64% of 76.55% in the first cycle to 86,19% in the second cycle, the aspect of confidence increased by 10,62% of 71.56% in the first cycle to 82.18% in the second cycle, and on aspects of satisfaction increased by 14,88% of 71,79% in the first cycle to 86.67% in the second cycle. Learning outcome increased by 14,29% of 71,42 in the first cycle to 85,71 in the second cycle. This result indicate problem based learning model can improve motivation and student learning outcomes.Penelitian ini bertujuan untuk meningkatkan motivasi dan hasil belajar siswa menerapkan model Problem Based Learning. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Subjek penelitian adalah siswa kelas IV SD Inpres Bangkala III Kota Makassar tahun pelajaran 2016/2017. Data penelitian diperoleh melalui observasi dan tes. Hasil penelitian ini terjadi peningkatan motivasi siswa pada keempat aspek dengan rincian, pada aspek attention sebesar 11,28% dari 73,04% pada siklus I menjadi 84,32% pada siklus II, pada aspek relevance meningkat sebesar 9,64% dari 76,55% pada siklus I menjadi 86,19% pada siklus II, pada aspek confidence meningkat sebesar 10,62% dari 71,56% pada siklus I menjadi 82,18% pada siklus II, dan pada aspek satisfaction meningkat sebesar 14,88% dari 71,79% pada siklus I menjadi 86,67% pada siklus II. Hasil belajar meningkat sebesar 14,29% dari 71,42% pada siklus I menjadi 85,71% pada siklus II. Hasil ini menunjukkan bahwa model Problem Based Learning dapat meningkatkan motivasi dan hasil belajar siswa.